An Overview of Valuable Scientific Models for Diabetes Mellitus - Akash, Muhammad S. H.; Rehman, Kanwal; Chen, Shuqing (Current Diabetes Reviews, 2013)
Diabetes mellitus is one of the major clinical problems worldwide. Previously, most of the investigational studies for identification of disease and new therapies were based on animal studies; however, present research methods involve high throughput screening, molecular targeting, nanotechnology for recent discovery of drugs and disease identification to combat against hazardous diseases like diabetes mellitus. In this review, we have depicted outlines enfolding various disease-specific animal modeling, sensing technologies, biomarker analysis, and novel scientific techniques that could be helpful in exploring the impending strategies for diabetes detection and treatment. To conclude, we believe that endorsement and upgrading of such novel high throughput screening assays and nanotechnology described herein may surely represent a significant improvement in the capability for screening and identifying the population at elevated risk of expected diabetes. Thereby in future, appreciation of such investigational techniques and technologies including metabolomics and genetic screening may help in early prediction of diabetes in patients at risk and may display a significant improvement over the researchers conducted after the declaration of the disease.
Keywords: oxidative stress